2020
DOI: 10.1177/2325967119895248
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Abnormal Limb Kinetics at 6 Months After Anterior Cruciate Ligament Reconstruction Have an Increased Risk of Persistent Medial Meniscal Abnormality at 3 Years

Abstract: Background: Several reports have shown that altered biomechanics after anterior cruciate ligament reconstruction (ACLR) are associated with the development of posttraumatic osteoarthritis. However, it is not fully understood whether altered biomechanics are associated with meniscal changes after ACLR. Purpose: To investigate changes in gait and landing biomechanics over a 3-year period and their correlation with meniscal matrix alterations present before and after ACLR through use of magnetic resonance T1ρ/T2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Therefore, there is a more compelling need to improve diagnostic techniques in order to detect PTOA at an early stage. T2 mapping has made the greatest strides in the evaluation of cartilage degeneration, which is a well-established early indicator of PTOA in patients after ACLR [16][17][18]. However, mean T2 6 BioMed Research International value analysis is somewhat subject to many common limitations, such as dependency of loading [19], sequence type [20], or parameter selection [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a more compelling need to improve diagnostic techniques in order to detect PTOA at an early stage. T2 mapping has made the greatest strides in the evaluation of cartilage degeneration, which is a well-established early indicator of PTOA in patients after ACLR [16][17][18]. However, mean T2 6 BioMed Research International value analysis is somewhat subject to many common limitations, such as dependency of loading [19], sequence type [20], or parameter selection [21].…”
Section: Discussionmentioning
confidence: 99%
“…6,10,11 These persistent kinetic asymmetries may increase risk of a secondary ACL injury 24 and/or contribute to knee degenerative changes. 11,25,26 As a result, there appears to be a need to explore novel rehabilitation approaches that could potentially more effectively target these persistent kinetic asymmetries. For instance, providing visual feedback related to side-to-side differences in limb loading during movement performance may be particularly effective for promoting inter-limb kinetic symmetry and minimizing maladaptive changes in an athlete's movement pattern following ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hamstrings weakness after ACL reconstruction may alter knee mechanics during gait [14]. This creates aberrant adaptations, shifting cartilage loading and therefore contributing to the development of joint degenerative process [38][39][40]. In addition, the presence of hamstrings weakness after surgery seems to be related to the kind of rehabilitation undertaken by the patients [41], thus, early postoperative approaches aiming at targeting hamstrings strengthening and restoring normal gait from the first phases may be helpful in the long-term morphofunctional recovery perspective.…”
Section: Discussionmentioning
confidence: 99%